(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article discusses the concept of information security, its general meaning, ways to strengthen it, considers ways to protect personal data, considers the concept of information security. Some advice is given to ordinary users.